Teachers' Perspectives on Global Warning in Mathematics Learning - Prihaswati, Martyana; Yuliyanto, Eko (Education, Science, and Technology International Conference, 2024)
Global warming is a natural phenomenon that urgently needs to be repaired to ensure the survival of creatures on Earth. To overcome this, the entire community must have an understanding of global warming, especially in the field of education. Before providing knowledge to the public, It is necessary to know the teacher's perspective as an educational facilitator regarding integrated learning on global warming. This research describes teachers' perspectives regarding global warming, especially in mathematics learning. This research is qualitative research with descriptive methods. The sample used was twelve high school mathematics teachers in Semarang City consisting of young and senior teachers to gain understanding from different points of view. Data collection uses an interview instrument. That instrument has received validation from experts before. The research results show the possibility of using the global warming phenomenon to realize a low-carbon society in Mathematics learning. However, there are difficulties in integrating it into Mathematics learning. It is necessary to develop a learning model that applies global warming to Mathematics learning so its implementation is evident.